Chemical synthesis of peptidoglycan mimetic–disaccharide-tetrapeptide conjugate and its hydrolysis by bacteriophage T5, RB43 and RB49 L-alanyl-D-glutamate peptidases - Azev,Viatcheslav; Chulin,Alexey; Molchanov,Maxim; Prokhorov,Dmitry; Mikoulinskaia,Galina; Uversky,Vladimir N.; Kutyshenko,Viktor (PeerJ, 2021)
Background Endolysins of a number of bacteriophages, including coliphages T5, RB43, and RB49, target the peptidoglycans of the bacterial cell wall. The backbone of these bacterial peptidoglycans consist of alternating N-acetylglucosamine and N-acetylmuramic acid residues that is further “reinforced” by the peptide subunits. Because of the mesh-like structure and insolubility of peptidoglycans, the processes of the peptidoglycan binding and hydrolysis by enzymes cannot be studied by spectral methods. To overcome these issues we synthesized and analyzed here one of the simplest water soluble peptidoglycan mimetics. Methods A compound has been synthesized that mimics the peptidoglycan fragment of the bacterial cell wall, N-acetylglucosaminyl-β(1-4)-N-acetylmuramoyl-l-alanyl-γ-d-glutamyl-l-alanyl-d-alanine. NMR was used to study the degradation of this peptidoglycan mimetic by lytic l-alanoyl-d-glutamate peptidases of colibacteriophages T5, RB43, and RB49 (EndoT5, EndoRB43, and EndoRB49, respectively). Results The resulting glycopeptide mimetic was shown to interact with the studied enzymes. Its hydrolysis occurred through the bond between l-Ala and d-Glu. This artificial substrate mimetic was hydrolyzed by enzymes at different rates, which decreased outside the pH optimum. The EndoT5 demonstrated the lowest hydrolysis rate, whereas the EndoRB49-driven hydrolysis was the fastest one, and EndoRB43 displayed an intermediate potency. These observations are consistent with the hypothesis that EndoRB49 is characterized by the lowest selectivity, and hence the potentially broader spectrum of the peptidoglycan types subjected to hydrolysis, which was put forward in the previous study. We also show that to hydrolyze this glycopeptide mimetic, enzymes approach the glycopeptide near the methyl groups of all three alanines.
Keywords: Peptidoglycan mimetic; Bacteriophage; Disaccharide-tetrapeptide conjugate; Chemical synthesis; NMR spectroscopy; Substrate hydrolysis; EndoT5; EndoRB43; EndoRB49; Endolysin